Food Consumption Patterns and Hypertension in Communities in the Martapura River Basin, Indonesia - Mahdalena, Mahdalena; Mahpolah, Mahpolah; Suroto, Suroto (Tropical Health and Medical Research, 2026)
Hypertension is a major risk factor for cardiovascular disease and remains a public health problem in Indonesia, including South Kalimantan. Diet plays a significant role in the development of hypertension, particularly in communities living in river basins characterized by high sodium and low fiber consumption. This study aims to analyze the relationship between dietary patterns and the incidence of hypertension in communities along the Martapura River Basin, South Kalimantan. The study, conducted in 2025, used a cross-sectional design with 260 purposively selected respondents. Data were collected through interviews using a structured questionnaire and blood pressure measurements. The Spearman test showed a significant association between the consumption of fatty foods (Rho=0.323; p=0.000), salty foods (Rho=0.341; p=0.000), fruit (Rho=0.575; p=0.000), and vegetables (Rho=0.477; p=0.000) and the incidence of hypertension. High sodium consumption and low fruit and vegetable consumption are determinants contributing to the high prevalence of hypertension in the Martapura River Basin community. This study emphasizes the need for contextual public health interventions through nutrition education and increased access to healthy foods to reduce the burden of hypertension in the region.